Comparison of the Dick and Carey and ADDIE Instructional Design Models in Islamic Religious Education Learning - Latifa Khusnul Fatikhah; Muhammad Aliy Madani; M. Rizwal Fazar; Sisca Yolanda Aulia; Winda Yanti; Rahmad Hulbat (PT Barkah Ilmi Fiddunya, 2026)
This research is motivated by the importance of using systematic instructional design models to improve the effectiveness of the learning process in Islamic Religious Education (PAI). In practice, educators need a model that can help them design learning in a structured manner so that learning objectives can be achieved optimally. Two models that are often used in instructional development are the Dick and Carey model and the ADDIE model. Both are known as systematic models, yet they have different stages and characteristics in their application to PAI learning. Based on this background, the focus of this study is to compare the Dick and Carey instructional design model and the ADDIE model in Islamic Religious Education learning. This study aims to identify the steps of the Dick and Carey model, the steps of the ADDIE model, their similarities and differences, as well as the strengths and weaknesses of each model in their application to PAI learning. The research method used is qualitative research with a library research approach. The data were obtained from various literature sources such as books, scientific journals, and articles relevant to the Dick and Carey and ADDIE instructional design models. The data were then analyzed using a descriptive-comparative method to identify the characteristics, similarities, and differences between the two models. The results of the study indicate that the Dick and Carey model has ten detailed and systematic steps that can help teachers design learning in a structured and in-depth manner. Meanwhile, the ADDIE model has five main stages Analysis, Design, Development, Implementation, and Evaluation which are simpler and more flexible to apply. Both models share similarities in their systematic approach but differ in the level of detail of the steps and the flexibility of their implementation in PAI learning